Induction of HGF and VEGF in hepatic regeneration after hepatotoxin-induced cirrhosis in mice - (:unkn) unknown (My University, 2011)
Background/Aims: Liver cirrhosis is the irreversible end-result of fibrous scarring and hepatocellular regeneration, characterized by diffuse disorganization of normal hepatic structure by regenerative nodules and fibrotic tissue. In this study, we elucidated the role of hepatocyte growth factor (HGF) and vascular endothelial growth factor (VEGF) in liver regeneration. Methodology: The study was conducted as an experimental laboratory investigation using a mouse model of lethal liver cirrhosis induced by carbon tetrachloride (CCl4), dimethylnitrosamine (DMN) and D-galactosamine (D-gal) administrations. Results: Liver morphology showed fibrosis/cirrhosis in all groups, but to a different extent, as confirmed by the rise in serum transaminase levels. The immunolocalization of VEGF and HGF, and homogenate levels of HGF and serum levels of VEGF, were also analyzed. Liver fibrosis/cirrhosis was more severe in CCl4-treated mice. In cirrhotic livers, immunostaining for HGF was weak and the HGF content of liver tissue was lower. Strong immunoreactivity for VEGF was observed when hepatotoxins were administered, however as cirrhosis became apparent immunoreactivity was reduced. Blood VEGF levels increased gradually. Conclusions: Our results suggest possible involvement of VEGF in angiogenesis of cirrhotic liver. VEGF might be required for reconstruction of hepatic cells and sequentially participates in liver regeneration by facilitating hepatocyte proliferation. HGF production is supposed to be induced in the necrotic liver during regeneration and severe tissue damage followed by cirrhosis might account for low homogenate HGF levels. © H.G.E. Update Medical Publishing S.A.
Keywords: Carbon tetrachloride; Cirrhosis; D-galactosamine; Dimethylnitrosamine; Fibrosis; Hepatic regeneration